Meningkatkan Ekonomi Masyarakat Melalui Akad Kemitraan Badan Usaha Milik Pesantren Hasan Jufri Bawean Gresik - Najiha, Ulfatun; Barakah, Ainun; Idaroh, Bella (CENDEKIA: Jurnal Studi Keislaman, 2024)
Pesantren Hasan Jufri is not only an Islamic educational institution, but also a driving force in improving the community's economy. Therefore, this study describes the following research focus: 1) How does Pesantren Hasan Jufri try to improve the community's economy? 2) What are the state-owned enterprises (BUM) of Pesantren Hasan Jufri that support efforts to improve the community's economy? 3) What are the partnership agreements used by BUM- Pesantren Hasan Jufri to improve the community's economy. This study aims to. 1) Find out the efforts of Pesantren Hasan Jufri in improving the community's economy. 2) Find out what BUM-pesantren Hasan Jufri supports efforts to improve the community's economy. 3) Find out what cooperation agreements are used by BUM-pesantren Hasan Jufri to improve the community's economy. The type of research is descriptive qualitative research. The data in this study were obtained from primary and secondary data. The techniques used in data collection were observation, interview, and documentation techniques. Then analyzed by means of data reduction, data presentation, and then drawing conclusions. The data validity checking technique uses observation extension, triangulation, and increased persistence. The results of this study are: 1) Efforts by Hasan Jufri Islamic boarding school to improve the community's economy: first, opening up employment opportunities by prioritizing alumni and potential communities. Second, the establishment of a business entity that is run through a cooperation agreement between Hasan Jufri Islamic boarding school and the community. 2) Hasan Jufri BUM-Islamic boarding school that supports efforts to improve the community's economy: Main Store, stalls, printing, student equipment stores, Barbershops, hotels, printing, agriculture, and laundry. 3) Partnership agreements used in Hasan Jufri BUM-Islamic boarding school to improve the community's economy: Musyarakah, ijarah, muzara'ah, mukhabarah, wakalah bil ujrah. mudharabah and Jualah.